2004
DOI: 10.1021/ol048013v
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the Hoogsteen Edge of 2‘-Deoxyguanosine:  Consequences for G-Quadruplex Formation

Abstract: The synthesis and self-assembling properties of 8-aryl-2′-deoxyguanosine derivatives are described. Our studies suggest that a properly placed acetyl group can increase the stability and specificity of the resulting G-quadruplex supramolecules by enhancing noncovalent interactions such as hydrogen bonds and π-stacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 20 publications
0
61
0
Order By: Relevance
“…Compound 1 was synthesized and purified as previously reported. 31 NMR spectra were recorded on spectrometers equipped with either a 5 mm BBO or a TXI probe, with nominal frequencies of 500.13 MHz for proton and 125 MHz for carbon respectively. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 procedure for the AMBER force field, as implemented in RED III.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compound 1 was synthesized and purified as previously reported. 31 NMR spectra were recorded on spectrometers equipped with either a 5 mm BBO or a TXI probe, with nominal frequencies of 500.13 MHz for proton and 125 MHz for carbon respectively. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 procedure for the AMBER force field, as implemented in RED III.…”
Section: Methodsmentioning
confidence: 99%
“…30 The Davis group have also reported that a 4T-SGQ or hexadecamer could be form via the putative picrate- 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 We have developed an alternative approach towards modulating the structure of SGQs that relies in replacing the H8 in the guanine moiety with a functionalized phenyl group. 31 The position of the functional group on the phenyl ring enables modulation of the molecularity and stability (thermal and kinetic) of the resulting supramolecules. For example, in the presence of potassium cations the mAG (metaacetylphenyl) scaffold promotes the formation of a four-tetrad (4T) SGQ or hexadecamer in both organic and aqueous environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have shown that functional groups within an 8-phenyl ring can lead to supramolecular complexes with higher stability. 7 Since Shaughnessy's method 9 of using the easily prepared 8-bromo-2′-deoxyguanosine 10 and commercially available boronic acids had proven successful in the synthesis of 8-aromatic-2′-deoxyguanosine analogues (8-ArdG), 7 we decided to apply it to the synthesis of 8-(HetAr)dG targets. However, although the method is useful in the coupling of a variety of heterocycles vide infra, we quickly realized that we needed to use a different method to couple the 2-pyridyl moiety.…”
mentioning
confidence: 99%
“…Through Hoogsteen hydrogen bonding, four nonadjacent guanines can associate with one another, forming a guanine tetrad. Furthermore, these guanine tetrads are capable of stacking upon one another, establishing a G-quadruplex (Gubala, 2004). These structures occur naturally throughout the human genome, most notably in telomeres, which are found at the ends of chromosomes, as well as in the promoter regions of an estimated 43% of all genes, including VEGF.…”
Section: Oligonucleotide Therapymentioning
confidence: 99%